Assessing entrepreneurial activity, aspirations and attitudes in Kazakhstan - O'Callaghan, R.; Yergozha, L. (Nazarbayev University, 2014)
Entrepreneurship remains a priority in most economies, and particularly so in Kazakhstan as recognized in the 2050 Strategy document proclaimed by President Nazarbayev. Evidence shows that the growth engines of an economy are not large companies, but the many entrepreneurs who start new businesses. NUGSB has recently joined GEM (The Global Entrepreneurship Monitor), the largest ongoing research project on Entrepreneurship in the world. The project assesses the motives and aspirations of (potential) entrepreneurs and the attitudes of those around them, i.e. the climate for entrepreneurship in society [1]. Nearly 100 "National Teams" from every corner of the globe participate in the project. NUGSB is now the National Team of Kazakhstan.
Keywords: entrepreneurship; economy; attitudes; project